Islamic Scholars Influence on Western Scientific Discourse During the Medieval Era - Lumban Gaol*, Ebeneser Lumban (Riwayat: Educational Journal of History and Humanities, 2024)
This study explores the substantial influence of Muslim scholars on the intellectual progress of Western society during the Medieval Era. By examining the dynamic relationship between Arab-Islam and European-Christianity, this research emphasizes the significant impact of Muslim scholars in various fields such as philosophy, science, astronomy, art, and literature. Utilizing historical methods, the study uncovers how Islam played a crucial role in shaping the development of scientific discourses in the West since the 11th century. Toledo and Sicily functioned as pathways for the Latinization of Arabic texts, extending initiatives from the Abbasid Caliphate period in the 8th century AD, particularly the translation of Greek texts into Arabic. Emphasizing the collaborative role between Islamic and Western civilizations, this research underscores that amid the historical realities of Islamic-Christian tension and conflict that marked the Middle Ages, interfaith interaction and cooperation could foster scientific progress. In this context, Islamic influence emerges as a key factor in comprehending the reciprocal exchange of ideas and knowledge that simultaneously moulded these two cultures.